Esophageal stricture due to recurrent mucositis in a patient with acute lymphoblastic leukemia - Karadağ-Öncel, Eda; Kenç, Senay; Aytaç, Selin; Aydemir, Yusuf; Hızal, Gülin; Yüce, Aysel; Kara, Ateş (The Turkish Journal of Pediatrics, 2013)
An esophageal stricture is one of the complications that may develop during cancer treatment in children. Although more commonly associated with radiotherapy, recurrent mucositis has also been implicated. Presented herein is a case of a patient with acute lymphoblastic leukemia who suffered recurrent attacks of severe mucositis. Initial management of ensuing dysphagia included antifungal treatment for candida esophagitis. A subsequent upper endoscopy due to persistence of dysphagia revealed the presence of an esophageal stricture. Our aim in presenting this case is to emphasize the importance of considering a diagnosis of esophageal stricture in patients receiving anti-cancer treatment; early endoscopic intervention may be warranted in some patients.